Pengaruh Radiasi Panas Area Bukaan terhadap Kenyamanan Termal pada Gedung Sekolah X - Tri Wulan Sari; Muhammad Daffa Rafliansyah; Dyah Nurwidyaningrum; Qori Febrianti; Sujito Sujito; Jonathan Saputra (Universitas Garut, 2025)
Thermal comfort is one of the key factors in supporting the teaching and learning process in classrooms, especially in tropical regions like Indonesia, which experience high solar radiation intensity. This study aims to analyze the effect of heat radiation from opening areas on thermal comfort in School Building X. The method involved measuring the dimensions of the building's openings and facades to calculate the Window to Wall Ratio (WWR), as well as determining the Solar Factor (SF) and Shading Coefficient (SC) based on SNI 03-6389-2020. The heat radiation value (Qf”) was calculated for the east and west orientations, which receive the most direct sunlight exposure. The results showed that the highest radiation occurred on the west side at 18.91 W/m² and the east side at 16.42 W/m². Meanwhile, the north and south sides had no Qf” value due to the absence of window openings (WWR = 0). The increase in indoor temperature caused by radiation through openings has a direct impact on the thermal comfort of students, teachers, and university students using the classrooms. Therefore, passive design strategies such as shading and the use of low-E glass are highly recommended to reduce heat load and create a comfortable learning environment.